Internal Factors Affecting the NPL of State-Owned Commercial Banks - Mohammad Sofyan; Bambang Heru Purwanto (Yayasan Ilomata, 2023)
Banking in Indonesia generally relies on loan interest income as the primary income in financing its operations. Not all credit extended is risk-free; some have sizable risks and can threaten the bank’s health. So to measure a bank's ability to overcome failure to take credit from debtors, the NPL ratio can be used. This study aims to analyse the influence of internal factors, namely: CAR, LDR, NIM, and OEOI, on NPLs of State-Owned Commercial Banks during 2015-2022. The research was conducted using a qualitative descriptive method with panel data using the financial statements of Bank BRI, Bank BNI, Bank Mandiri, and Bank BTN during 2015 - 2022. The results of this study indicate that CAR and BOPO have a significant positive effect on NPL, while LDR and NIM have a significant negative effect on NPL.